2015
DOI: 10.1590/0101-60830000000045
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative experiences in bipolar disorder II: Are they related to childhood trauma and obsessive-compulsive symptoms?

Abstract: Objective: The aim of this study is to investigate the presence of dissociative symptoms and whether they are related to childhood trauma and obsessive--compulsive symptoms in bipolar disorder type II (BD-II). Methods: Thirty-three euthymic patients (HDRS<8, YMRS<5) and 50 healthy subjects were evaluated by SCID-I and SCID-NP. We excluded all first and second-axis comorbidities. All patients and healthy subjects were examined with the Dissociative Experiences Scale (DES), Childhood Trauma Questionnaire (CTQ-53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Specifically, ‘Arm rigidity’ , an item of physical dissociation, was associated with the MDQ score in BD I patients, indicating that the drive of the behavioral activation system was higher and was associated with mania in this disorder [ 58 ]. ‘Age regression’ , an item of consciousness dissociation, was associated with the MDQ score in BD II patients, consistent with the findings of pronounced childhood trauma and related dissociative symptoms, and the manic-related anxiety characteristic to this disorder [ 59 , 60 ]. ‘Mosquito hallucination’ , often a manifestation of irritability, was associated with the MDQ score in healthy volunteers, which was partly in line with that the auditory hallucinations were regularly seen in bipolar disorder patients, especially during their manic episodes [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 81%
“…Specifically, ‘Arm rigidity’ , an item of physical dissociation, was associated with the MDQ score in BD I patients, indicating that the drive of the behavioral activation system was higher and was associated with mania in this disorder [ 58 ]. ‘Age regression’ , an item of consciousness dissociation, was associated with the MDQ score in BD II patients, consistent with the findings of pronounced childhood trauma and related dissociative symptoms, and the manic-related anxiety characteristic to this disorder [ 59 , 60 ]. ‘Mosquito hallucination’ , often a manifestation of irritability, was associated with the MDQ score in healthy volunteers, which was partly in line with that the auditory hallucinations were regularly seen in bipolar disorder patients, especially during their manic episodes [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 81%
“…DS were comparable in BD and schizophrenia in a single study ( 43 ). However, DS scores were significantly higher in patients with BD than in their asymptomatic first-degree relatives ( 23 ) and were consistently higher in BD than in healthy controls ( 28 , 33 , 34 , 37 , 39 , 43 ).…”
Section: Resultsmentioning
confidence: 88%
“…Of the six studies providing estimates of clinically significant DS in BD, as indicated by symptom scores above a specified cut-off, five yielded very similar values in the range of 10–20% ( 18 , 33 , 34 , 39 , 43 ). A single study yielded a much higher estimate of 51%, but in this study, the control group also reported high levels of DS (24%), suggesting concerns related to methodology or sample selection ( 28 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Growing empirical evidence has indicated that dissociative experiences are pervasive within clients with SMIs; heightened dissociation is commonly reported by individuals who received diagnoses of psychosis , bipolar disorder and personality disorders . In line with evidence suggesting that dissociation is a common sequela of adverse and/or traumatic life experiences, many empirical studies have demonstrated that individuals with SMIs exposed to childhood adversity (e.g.…”
Section: Introductionmentioning
confidence: 97%